Development of diagnostic assays for differentiation of atypical Aeromonas salmonicidavapA type V and type VI in ballan wrasse (Labrus bergylta, Ascanius). Issue 6 (25th January 2021) - Papadopoulou, Athina; Davie, Andrew; Monaghan, Sean J.; Migaud, Herve; Adams, Alexandra
Abstract: Aeromonas salmonicida ( As ) is a highly heterogeneous bacterial species, and strains' host specificity has been reported. Ballan wrasse ( Labrus bergylta Ascanius, 1767) is susceptible to atypical As (a As ) vapA type V and type VI in Scotland and Norway. Identification of the bacterium is achieved by culture and molecular techniques; however, the available methods used to distinguish the As types are costly and time‐consuming. This paper describes the development of a PCR and a restriction enzyme assay for the detection of a As vapA type V and type VI in ballan wrasse, respectively. Type V‐specific primers were designed on conserved regions of the vapA gene, and the restriction enzyme assay was performed on the PCR products of the hypervariable region of vapA gene for the detection of type VI isolates. Amplification product was produced for type V (254 bp) and restriction bands (368 and 254 bp) for type VI isolates only. In addition, the assays detected type V and type VI isolates in spiked water samples and type V in diagnostic tissue samples. The assays are fast, specific and cost‐effective and can be used as specific diagnostic tools for cleaner fish, to detect infectious divergence strains, and to manage and mitigate a As disease outbreaks through vaccine development.